Winter solstice eaudiobook - Hilderbrand, Elin (Winter, 2017)
*The USA Today Bestseller* Raise one last glass with the Quinn Family at the Winter Street Inn. It's been too long since the entire Quinn family has been able to celebrate the holidays under the same roof, but that's about to change. With Bart back safe and sound from Afghanistan, the Quinns are preparing for a holiday more joyous than any they've experienced in years. And Bart's safe return isn't the family's only good news: Kevin is enjoying married life with Isabelle; Patrick is getting back on his feet after paying his debt to society; Ava thinks she's finally found the love of her life; and Kelly is thrilled to see his family reunited at last. But it just wouldn't be a Quinn family gathering if things went smoothly. A celebration of everything we love—and some of the things we endure—about the holidays, WINTER SOLSTICE is Elin Hilderbrand at her festive best. Follow the Quinn family through the entire Winter Street Series: Winter Street Winter Stroll Winter Storms Winter Solstice